2018
DOI: 10.1007/s00004-018-0388-6
|View full text |Cite
|
Sign up to set email alerts
|

A Metrological Study of the Late Roman Fort of Umm al-Dabadib, Kharga Oasis (Egypt)

Abstract: This article contains a first metrological analysis of the Late Roman Fort of Umm al-Dabadib, built at the beginning of the 4th century AD at the outskirts of the Kharga Oasis, in the Egyptian Western Desert. This site is currently under study by the Italian Archaeological Mission to Umm al-Dabadib; after completing the 3D survey of the building, the team moved to the study of its dimensional patterns. The resulting 3D model was tested for the use of Roman and Egyptian units of measurement, and revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Briefly described in the early Twentieth Century (Beadnell 1909), its real extent was only revealed in 1998 (Rossi 2000); it was then studied for the first time in some detail between 2001 and 2007 by the North Kharga Oasis Survey (NKOS, Rossi and Ikram 2018). Between 2012 and 2014, its agricultural system was the object of a specific study by the Old Agricultural Sites and Irrigation Systems (OASIS) project of the MUSA Centre of the Federico II University of Naples (Fassi et al 2015;Rossi 2016; Rossi forthcoming-a); it is now the object of the multi-disciplinary project Living In a Fringe Environment (LIFE), jointly carried out by the Politecnico di Milano and the MUSA Centre and funded by the ERC CoGrant 681673 Rossi forthcoming-b;Rossi and Fiorillo 2018;Rossi and Magli forthcoming).…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly described in the early Twentieth Century (Beadnell 1909), its real extent was only revealed in 1998 (Rossi 2000); it was then studied for the first time in some detail between 2001 and 2007 by the North Kharga Oasis Survey (NKOS, Rossi and Ikram 2018). Between 2012 and 2014, its agricultural system was the object of a specific study by the Old Agricultural Sites and Irrigation Systems (OASIS) project of the MUSA Centre of the Federico II University of Naples (Fassi et al 2015;Rossi 2016; Rossi forthcoming-a); it is now the object of the multi-disciplinary project Living In a Fringe Environment (LIFE), jointly carried out by the Politecnico di Milano and the MUSA Centre and funded by the ERC CoGrant 681673 Rossi forthcoming-b;Rossi and Fiorillo 2018;Rossi and Magli forthcoming).…”
Section: Case Studiesmentioning
confidence: 99%
“…2). The ensuing results allowed the team to start a metrological research into the planning and building methods used by the ancient builders, which otherwise would have been impossible (Rossi and Fiorillo 2018).…”
Section: Case Studiesmentioning
confidence: 99%
“…Archaologists comparing written notes with one another, during the 2018 Dutch-Italian excavation at Saqqara of the Museo Egizio, Turin and the Rijksmuseum van Oudheden, Leiden of items are used just as 'better' (more attractive and efficient) images in comparison with photographs, but they are rarely exploited to really enhance specific characteristics of the object which would otherwise be invisible or undetectable (e.g. Rossi and Fiorillo 2018).…”
Section: Fieldwork and Digital Toolsmentioning
confidence: 99%
“…In this case, for instance, it immediately showed that the width of the rooms at level 0 corresponds to 5.5 or 6 c; that of the central court probably to 13.5 c; that the east tower measured 3.5 c × 4.5 c, and the west tower 3 c × 4 c (Figure 9). A detailed metrological analysis, including a discussion on the units of measurement employed, will appear elsewhere [16,17].…”
Section: The Metric Analysis Of the Fortmentioning
confidence: 99%